2007
DOI: 10.1080/08860220701459642
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in Chronic Hemodialysis Patients: The Impact of Depression and Anemia

Abstract: The questionnaire showed a high prevalence of insomnia in the dialytic population. The study also attributes a predictive role in sleep quality to gender, depression, dialytic duration, and hemoglobin levels. The data indicate that in the management of insomnia in this patient group, anemia and depression, both of which are potentially correctable, should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
70
5
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 20 publications
13
70
5
8
Order By: Relevance
“…These results were in agreement with many observations reported by the other investigators. 7,13,14 As regard to phosphate level and sleep disorders there was positive correlation between phosphate level and brief arousal index and PLM in all the groups (r ¼ 0.367, p ¼ 0.0004 and r ¼ 0.384, p ¼ 0.0002), respectively, While negative correlation was found between phosphate level and sleep efficiency in all groups (r ¼ À0.4131, p50.0001 and r ¼ À0.3987, p50.0001), respectively. On the other hand, sleep disorders were also reported in many cases with chronic illness such as liver cirrhosis and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with many observations reported by the other investigators. 7,13,14 As regard to phosphate level and sleep disorders there was positive correlation between phosphate level and brief arousal index and PLM in all the groups (r ¼ 0.367, p ¼ 0.0004 and r ¼ 0.384, p ¼ 0.0002), respectively, While negative correlation was found between phosphate level and sleep efficiency in all groups (r ¼ À0.4131, p50.0001 and r ¼ À0.3987, p50.0001), respectively. On the other hand, sleep disorders were also reported in many cases with chronic illness such as liver cirrhosis and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…29 The Chinese version of the PSQI has been used for the study of sleep quality in Taiwan's HD patients. 7,8 The AIS was used to assess sleep complaints and to identify possible cases of clinically significant insomnia. The AIS consists of eight items.…”
Section: Measurement Of Sleep Qualitymentioning
confidence: 99%
“…[2][3][4][5][6] Taiwan-based studies showed a high prevalence of insomnia (66.6%) and poor sleep quality (74.4%) in ESRD patients. 7,8 Many conditions may cause sleep disturbances in these patients, including constraints in life, metabolic abnormalities, dietary restrictions, dyspnea, fatigue, nocturnal cramps, advanced age, hypocapnia accompanied by metabolic acidosis, neuropathic pain, and emotional problems. 9 Sleep disorders appear to be part of the ESRD and manifest as sleep-disordered breathing/ sleep apnea, 10,11 excessive daytime sleepiness (EDS), 12,13 periodic limb movement disorder (PLMD), and restless legs syndrome (RLS).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia correlated with the presence of depression, anxiety, anemia, primary sleep disorders such as restless legs syndrome, metabolic [23,25] and immunology distress [26]. It is questionable how dialysis therapy influences, directly or indirectly (through the co-morbidites state), the onset of insomnia in these patients.…”
Section: Discussionmentioning
confidence: 99%